EVALUATION OF THE EFFECTIVENESS OF HUMAN RESOURCES TRAINING AND DEVELOPMENT PROGRAMS IN THE PUBLIC SECTOR - Jamaluddin Jamaluddin (CV. Adiba Aisha Amira, 2025)
This research aims to evaluate the effectiveness of human resource (HR) training and development programs in the public sector through a comprehensive literature study. In an era characterized by rapid change and increasing complexity, developing human resource capacity is crucial for improving the performance of public organizations. The research method integrates academic sources and relevant practical reports to identify key factors influencing the success of training programs, as well as the most effective evaluation methods. The research results show that factors such as management support, program design that suits participants' needs, and an organizational culture that supports learning play a vital role in the success of training programs. Comprehensive evaluation, including pre- and post-training assessments, analysis of participant feedback, as well as on-the-job performance monitoring, was found to be effective in assessing training outcomes. This study concludes that holistic and continuous evaluation not only increases the effectiveness of HR training and development programs, but also contributes to improving the performance and efficiency of public sector organizations as a whole.